Sulh (mediation) in the Syariah court: some problems and prospects - Abdul Hak, Nora; Oseni, Umar Aimhanosi (Faculty of Law, Universiti Kebangsaan Malaysia, 2011)
Islamic law considers any court-annexed framework for the resolution of disputes as part of the case management role of the judge. This paper examines the status of the court-annexed mediation programme of the Shari'ah Court in Malaysia. Issues especially relating to the backlog of cases, led to the introduction of sulh (mediation) as court-annexed process with a view to acessing the problems, and their resolution. Overcoming these operational challenges identified will go a long way in reducing the backlog of cases in Shari'ah courts in Malaysia. A number of challenges are encountered in implementing this court annexed mediation.